Žodžio galo ir priegaidžių fonetinė evoliucija šiaurės žemaičių tarmėje - Pabrėža, Juozas (Baltistica, 1994)
PHONETIC EVOLUTION OF WORD END AND SYLLABLE ACCENTS IN THE NORTHERN ŽEMAITIAN DIALECT In this investigation an attempt is made to test if the accent, which is placed in the penultimate syllable, in the Northern Žemaitian dialect has any influence on the ending reduction. The analysis of the corpus of 4000 items has shown that word end reduction is greater after a circumflex accent. The drawn-out nature of the circumflex accent in the Northern Žemaitian dialect causes the concentration of the main energy on the distinctly drawn-out sound, weakening the intensity of the ending and as a result reducing it more. The vowel heard more distinctly after the acute accent, which in the dialect is most often realised as a broken one, apparently is determined by the nature of the broken accent itself: when the break is very distinct, the final vowel following it becomes more distinct as well. The investigation has also shown that ending reduction is significantly greater after voiceless and non-palatalized (‘hard’, ‘dark’) consonants.